Idiopathic Seidlmayer's Purpura: A Case Report - Maria Cristina Maggio; Fabrizia Ferraro; Saveria Sabrina Ragusa; Umberto Corpora; Giovanni Corsello (Karger Publishers, 2014)
Acute hemorrhagic edema of infancy (AHEI) was considered a rare form of Henoch-Schönlein purpura; however, it is now regarded as an independent disease typically involving patients aged 4-24 months. The authors describe the clinical case of a toddler aged 8 months, with skin erythematous pomphoid lesions, treated at home with topical steroids without benefits. The appearance of new lesions and the worsening of the previous skin signs induced the parents to drive the child to the hospital. The medical history revealed the administration of a vaccine dose 2 months before.